Subarrays of phased-array antennas for multiple-input multiple-output radar applications - Syahfrizal Tahcfulloh; Muttaqin Hardiwansyah (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
The subarray MIMO radar (SMIMO) is a multiple-input multiple-output (MIMO) radar with elements in the form of a sub-array that acts as a phased array (PAR), so it combines at the same time the key advantage of the PAR radar, which is high directional gain to increase target range, and the key advantage of the MIMO radar, i.e., high diversity gains to increase the maximum number of detected targets. Different schemes for the number of antenna elements in the transceiver zones, such as uniform and/or variable, overlapped and non-overlapped, significantly determine the performance of radars as virtual arrays (VARs), the maximum number of detected targets, the accuracy of target angle, detection resolution, SNR detection, and detection probability. Performance is also compared with the PAR, the MIMO, and the phased MIMO radars (PMIMO). The SMIMO radar offers great versatility for radar applications, being able to adapt to different shapes of the multiple targets to be detected and their environment. For example, for a transmit-receive with an antenna element number, i.e., M=N=8, the range of the number of detected targets for the SMIMO radar is flexible compared to the other radars. On the other hand, the proposed radar's signal-to-noise ratio (SNR) detection performance and detection probability (K=5, L=3) are both 1,999 and above 90%, which are better than other radars.